Analysis of Meteorological Data for La Selva Station by Applying the Biotic Pump Theory - Bunyard, Peter; Peña, Carlos; Díaz, Laura (TECCIENCIA, 2014)
This work sought to analyze the relationships among the atmospheric variables reported daily by the La Selva biological station, which is located on the mountain slopes of the Costa Rican Caribbean, covering 1614 hectares of tropical humid lowlands, through the biotic pump theory developed by Anastassia Makarieva and Victor Gorshkov, which states the importance of the participation of los forests during the process of generating winds in the intertropical convergence zone, being a dynamic and vital factor for the permanence of the hydrological cycle that fulfills the mission of delivering rains to the interior of the continents. In the biotic pump theory, Makarieva and colleagues postulate that the high rate of evapotranspiration is maintained by Tropical rainforests throughout the year and it gives way to a net force, which results from changes of the partial pressure of water vapor. These changes have a double element: first, the partial pressure of water vapor and, second, condensation. Upon combining these elements, temperature is reduced with altitude and the liberation by the vegetation of cloud condensation nuclei (CCN). The end result of the theory is a water vapor pump from the vegetation, through evapotranspiration onto the atmosphere, followed by condensation, which leads to upward acceleration, hence, on the vertical plane of the lower air mass. This work established the relationships among the thermodynamic variables insinuated by the biotic pump theory, using available information offered by La Selva station.